Systematic Review Of Point Of Care Testing In Emergency Care - Nurjannah Nurjannah (Jurnal Kedokteran Syiah Kuala, 2010)
Abstract. The study aims to review  systematically  the evidence of using Point of Care Testing (POCT) in Emergency Departments (EDs).  It will identify and qualitatively synthesise whether POCT in emergency care is safe, effective and has effective outcomes for patients. The systematic review was based on principles and guidelines  produced in the report by the National  Institute for Health Research {NIHR) Centre for Reviews and Dissemination (CRD), the University of York (2001) and the Critical  Review Advisory Group (CRAG), by the School·  of  Health  and Related   Research (ScHARR), the University of  Sheffield  (1996).  A  thorough and systematic  search strategy was adapted to identify, collate and .summanze a11  relevant studies the published research 1951   - 2008.There were 33 studies that met the inclusion criteria of the systematic review which consisted of 3 studies of Randomized Controlled Trial (RCT) design,   15 studies of diagnostic test design,  3 studies of before-and-after  design  and  12  articles of cohort design.  There  was clinical and methodological heterogeneity from all included studies.  Thus, non-quantitative synthesis was performed.  There is evidence that POCT in emergency care is safe, effective and bas effective outcomes for patients. In clinical outcomes,  POCT may provide an independent and significant predictor for serious adverse events and death.  However,  POCT seems to be unlikely to  reduce the mortality rate.  In  economical  outcomes, POCT  in  EDs  may decrease turnaround time and reduce unnecessary admission  to hospital,  in particular  to Intensive Care Unit (ICU) and Coronary Care Unit (CCU), but there are inconsistencies   in the results over reducing ED and hospital length of stay.(JKS2010;2:63-70)Key words: Point of Care Testing,EmergencyCare, EmergencyDepartment